High-resolution distance mapping in rhodopsin reveals the pattern of helix movement due to activation - Altenbach, Christian (National Academy of Sciences, 2008)
Site-directed spin labeling has qualitatively shown that a key event during activation of rhodopsin is a rigid-body movement of transmembrane helix 6 (TM6) at the cytoplasmic surface of the molecule. To place this result on a quantitative footing, and to identify movements of other helices upon photoactivation, double electron–electron resonance (DEER) spectroscopy was used to determine distances and distance changes between pairs of nitroxide side chains introduced in helices at the cytoplasmic surface of rhodopsin. Sixteen pairs were selected from a set of nine individual sites, each located on the solvent exposed surface of the protein where structural perturbation due to the presence of the label is minimized. Importantly, the EPR spectra of the labeled proteins change little or not at all upon photoactivation, suggesting that rigid-body motions of helices rather than rearrangement of the nitroxide side chains are responsible for observed distance changes. For inactive rhodopsin, it was possible to find a globally minimized arrangement of nitroxide locations that simultaneously satisfied the crystal structure of rhodopsin (Protein Data Bank entry 1GZM), the experimentally measured distance data, and the known rotamers of the nitroxide side chain. A similar analysis of the data for activated rhodopsin yielded a new geometry consistent with a 5-Å outward movement of TM6 and smaller movements involving TM1, TM7, and the C-terminal sequence following helix H8. The positions of nitroxides in other helices at the cytoplasmic surface remained largely unchanged.